(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
I was interested in the fact how foster parents with different social, cultural and educational background meet the requirements of leisure activities. This issue cannot be examined without considering the real environment in which children live. How do children living in their own families and children with similar social backgound usually spend their leisure time? To answer this question, I needed a control group of children to compare children in foster families to. Therefore I also asked the pupils (mostly living with their own families) of two primary schools about their leisure activities during my research. There were both disadvantaged and multiply disadvantaged children among the pupils. I made a comparison between the variety of leisure activities and the social contacts during the leisure activities in both groups: children living in foster families and children living with their own families.